Pharmacists’ Interventions in A Paediatric Haematology-Oncology Pharmacy: Do They Matter to Minimise Medication Misadventure? - Hesty Ramadaniati; Ya P. Lee; Jeffery D. Hughes; Lynne Emmerton (Indonesian Journal of Clinical Pharmacy, 2016)
Paediatric patients with cancer are a high-risk patient population for medication misadventures. This study aimed to document and evaluate the role of pharmacists’ interventions during dispensing-related activities in minimising the occurrence of medication misadventure in haematology-oncology patients. The primary investigator observed and documented all clinical interventions during dispensing-related activities performed by clinical pharmacists in a haematology-oncology pharmacy during 33-day. A total of 359 interventions were performed for 1028 patients. The rates of intervention were 20.04 per 100 medication orders and 34.92 per 100 patients. Provision of drug information was the most common interventions constituting more than three quarters of all interventions. According to therapeutic groups, cytotoxic antineoplastics made up more than half of all interventions. Of all interventions, 22 involved recommendations leading to changes in patients’ treatment (active interventions), and all recommendations were accepted. The top three medication errors were due to inappropriate dosing, labelling error, and unfulfilled indication. Clinical pharmacists’ intervention during dispensing in a paediatric haematology-oncology pharmacy improved medication safety and patient care by minimising the incidence of medication misadventures.Key words: Haematology-oncology, medication misadventure, paediatrics, pharmacists’ intervention Intervensi Farmasis pada Pasien Pediatrik di Apotek Hematologi-Onkologi: Apakah Farmasis dapat Mengurangi Kecelakaan dalam Pengobatan? Pasien kanker pediatrik merupakan kelompok pasien berisiko tinggi mengalami kecelakaan pengobatan. Penelitian ini bertujuan untuk mendokumentasikan dan mengevaluasi peran intervensi farmasis selama dispensing (peracikan dan penyerahan obat) obat untuk meminimalisir kecelakaan pengobatan pada pasien hematologi-onkologi. Peneliti utama mengobservasi dan mendokumentasikan intervensi klinis selama dispensing oleh farmasis klinis di sebuah apotek satelit hematologi-onkologi selama 33 hari. Sebanyak 359 intervensi diberikan pada 1028 pasien. Prevalensi intervensi sebesar 20,04 tiap 100 obat yang diresepkan dan 34,92 tiap 100 pasien. Pemberian informasi obat adalah intervensi yang paling umum diberikan (lebih dari tiga per empat dari semua intervensi). Berdasarkan terapetik obat, antineoplastik sitotoksik terkait dengan lebih dari setengah intervensi. Sebanyak 22 intervensi melibatkan rekomendasi yang mengarah pada perubahan pengobatan pasien (intervensi aktif) dan semua rekomendasi diterima oleh dokter. Adapun tiga besar kesalahan pengobatan disebabkan dosis tidak sesuai, kesalahan pelabelan, dan indikasi yang tidak terobati. Intervensi farmasis klinis selama dispensing di apotek satelit hematologi-onkologi pediatrik dapat meningkatkan keselamatan pengobatan dan asuhan pasien dengan meminimalisir kecelakaan pengobatan.Kata kunci: Hematologi-onkologi, intervensi farmasis, kecelakaan pengobatan, pediatrik